A glaring omission in Australia’s marine conservation planning - Hobbs, Jean-Paul (Pergamon, 2014)
The primary goal of Australia’s National Representative System of Marine Protected Areas(NRSMPA) is to establish a comprehensive, adequate and representative system of MPAs. This study identifies a glaring contradiction to this policy. The provinces of Christmas and Cocos Islands are among the most unique and threatened marine bioregions in Australia, yet receive no protection from the NRSMPA. The lack of protection appears to be due to difficulties with multiple governance arrangements and other political priorities. These issues have already caused biodiversity loss in the terrestrial environment of these bioregions. The Australian Government must include the Christmas and Cocos provinces in the NRSMPA other wise it risks irreversible loss of marine biodiversity in these unique bioregions.